Review and positions: Global production networks and labour - Rainnie, Alistair; Herod, A.; McGrath-Champ, S. (University of Hertfordshire Business School and W.S. Maney &Son Ltd, 2011)
Commodity chains that are global in extent have increasingly come to be seen as the defining element of the contemporary globalized world economy. Since the 1990s a body of theory - evolving from global commodity chain analysis to global value chain analysis to global production network analysis - has focused upon understanding how such commodity chains function. However, despite providing many important insights, these bodies of literature have generally suffered from a major deficiency in that they have failed to consider labour as an active agent capable of shaping such chains’ structure and geographical organization. Here, then, we present a case for locating more centrally labour, in production network analysis.